Characterization and molecular detection of pathogenicity and antibiotic resistance genes in Vibrio parahaemolyticus isolated from Pacific white shrimp - Muhammad Arif Mulya; Fachriyan Hasmi Pasaribu; Usamah Afiff; Munti Yuhana (Jurnal Akuakultur Indonesia, 2022)
ABSTRACT This study aimed to conduct the characterization and molecular detection of the pathogenicity and antibiotic-resistance genes in Vibrio parahaemolyticus, as the causative agent of vibriosis in Pacific white shrimp. The V. parahaemolyticus isolates were collected from the shrimp’s hepatopancreas, before biochemical test and polymerase chain reaction (PCR) sequencing of the 16S rRNA gene confirmation. The hemolysis test and PCR were applied to detect the presence of virulence genes, namely toxR, thermostable direct haemolysin (tdh), and tdh-related haemolysin (trh). The Kirby-Bauer method was used for characterizing the resistance patterns against ampicillin (AMP), tetracycline (TET), cyprofloxacin (CIP), enrofloxacin (ENR), and chloramphenicol (CHL). The biochemical tests and PCR-16SrRNA gene sequencing confirmed that 12 isolates belonged to V. parahaemolyticus that were further verified by amplification of the toxR gene in 382 bp (100% of the isolates). The alpha hemolysis activity was also confirmed by the amplicon of 199 bp in all isolates. All V. parahaemolyticus isolates showed their resistance to AMP and 42% of the isolates were TET-resistant. However, no resistance was shown to CIP, ENR, and CHL. The PCR-based analysis resulted a detectable resistance gene of ampC (42% of the isolates) and tetB (83% of the isolates). Keywords: antibiotics, shrimp, resistance, virulency, Vibrio parahaemolyticus ABSTRAK Penelitian ini bertujuan untuk melakukan karakterisasi dan deteksi molekular dari gen patogenisitas dan resistansi antibiotik pada Vibrio parahaemolyticus, agen penyebab vibriosis pada udang vaname. Isolat V. parahaemolyticus dikoleksi dari hepatopankreas, diuji secara biokimiawi dan selanjutnya dikonfirmasi dengan polymerase chain reaction (PCR)-sekuensing dari gen 16S rRNA. Tes hemolisis dan metode PCR diterapkan untuk mendeteksi keberadaan gen virulensi toxR, thermostable direct haemolysin (tdh) and tdh-related haemolysin (trh). Metode Kirby Bauer digunakan untuk karakterisasi pola resistansi terhadap ampisilin (AMP), tetrasiklin (TET), kloramfenikol (CHL), siprofloksasin (CIP) dan enrofloksasin (ENR). Uji biokimia dan sekuensing gen PCR-16SrRNA memastikan bahwa 12 isolat adalah V. parahaemolyticus yang selanjutnya diverifikasi dengan amplifikasi gen toxR berukuran 382 bp (100% isolat). Aktivitas alfa hemolisis juga dikonfirmasi dengan amplikon PCR (199 bp) di semua isolat. Seluruh isolat V. parahaemolyticus menunjukkan resistansinya terhadap AMP, 42% resistan TET, tidak ada resistansi yang ditunjukkan pada CIP, ENR dan CHL. Analisis berbasis PCR menghasilkan gen resistan yang terdeteksi dari gen ampC (42% isolat) dan gen tetB (83% isolat). Kata kunci: Antibiotik, udang, resistansi, virulensi, Vibrio parahaemolyticus